HOW READY ARE PEOPLE FOR CASHLESS SOCIETY? - Irwan Trinugroho; Hunik Sri Runing Sawitri; Muh Juan Suam Toro; Siti Khoiriyah; Arief Budi Santoso (University of Merdeka Malang, 2017)
Financial technology could be an effective tool to achieve financial inclusion. However, it neededa certain level of readiness of society. In this paper, we investigated the determinants of readinessin the implementation of digital financial services which led to cashless society. We did a surveyon 993 adults in a province in Indonesia using proportional sampling technique. Estimated usingordinary least square, our empirical results showed that readiness perception had high correlationwith the quality of supporting infrastructure. By taking into account some demographic factors,we found that more educated and younger people had high spirit to adopt this system. Evidenceshowed that men were more enthusiastic in using such technological-based system. However, wedid not find an evidence on the difference of readiness perception between those living in rural andthose living urban areas.